ISTIA’RAH IN THE STORY OF THE PROPHET NOAH AS AND THE IMPLICATIONS OF EDUCATIONAL VALUES - Naih Nurjanah (Gunung Djati Conference Series, 2023)
The use of metaphorical language is one of the skills used in various verses of the Qur'an to express meaning imaginatively. Even though the words of the Koran are frequently debated and recorded, most Muslims are unaware of the mysticism within them. It is necessary to reinterpret the miracle of the Al-Qur'an, which has numerous patterns and ways in each letter and verse, to avoid misinterpreting and misunderstanding the passage. Rhetoric, using a rhetorical methodology, is the scientific study investigating the nature of the wonders of the Qur'an. Several surahs in the Koran explain Noah's history as one of the prophets with the title Ulul al-Azmi. To avoid misconceptions and to evaluate the effect of metaphorically edited verses on the education of students, readers, and devotees of the Prophet Noah, peace be upon him; it is necessary to reexplain any such verses.